Plant-Derived Natural Biomolecule Picein Attenuates Menadione Induced Oxidative Stress on Neuroblastoma Cell Mitochondria - Kavindra Kumar Kesari; Anupam Dhasmana; Shruti Shandilya; Neeraj Prabhakar; Ahmed Shaukat; Jinze Dou; Jessica M. Rosenholm; Tapani Vuorinen; Janne Ruokolainen (MDPI AG, 2020)
Several bioactive compounds are in use for the treatment of neurodegenerative disorders, such as Alzheimer's and Parkinson's disease. Historically, willow (salix sp.) bark has been an important source of salisylic acid and other natural compounds with anti-inflammatory, antipyretic and analgesic properties. Among these, picein isolated from hot water extract of willow bark, has been found to act as a natural secondary metabolite antioxidant. The aim of this study was to investigate the unrevealed pharmacological action of picein. In silico studies were utilized to direct the investigation towards the neuroprotection abilities of picein. Our in vitro studies demonstrate the neuroprotective properties of picein by blocking the oxidative stress effects, induced by free radical generator 2-methyl-1,4-naphthoquinone (menadione, MQ), in neuroblastoma SH-SY5Y cells. Several oxidative stress-related parameters were evaluated to measure the protection for mitochondrial integrity, such as mitochondrial superoxide production, mitochondrial activity (MTT), reactive oxygen species (ROS) and live-cell imaging. A significant increase in the ROS level and mitochondrial superoxide production were measured after MQ treatment, however, a subsequent treatment with picein was able to mitigate this effect by decreasing their levels. Additionally, the mitochondrial activity was significantly decreased by MQ exposure, but a follow-up treatment with picein recovered the normal metabolic activity. In conclusion, the presented results demonstrate that picein can significantly reduce the level of MQ-induced oxidative stress on mitochondria, and thereby plays a role as a potent neuroprotectant.